Perlindungan Hukum terhadap Konsumen atas Perjanjian Pengikatan Jual Beli Berdasarkan Klausula Baku - Yudika Bagus Prayoga; Dhoni Martien; Khoirul Anwar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Discussion on legal protection for consumers regarding sales and purchase agreements based on standard clauses. The research was conducted using normative juridical methods. The results of the research concluded that legal protection for house sales and purchase agreements using standard clauses is that sales and purchase agreements that are usually made before the Deed of Sale and Purchase, can be canceled on the condition that the parties must know and agree with each other who will bind themselves in the agreement by including a clause that will override Article 1266 of the Civil Code, so that the conditions for canceling the PPJB can be carried out without the need for a judge's approval in court.